Generative design : visualize, program, and create with JavaScript in p5.js - Groß, Benedikt, 1980-; Bohnacker, Hartmut, 1972-; Laub, Julia, 1980-; Lazzeroni, Claudius, 1965- (Princeton Architectural Press, 2018)
Generative design, once known to insiders as a revolutionary method of creating artwork, models, and animations with programmed algorithms, has in recent years become a popular tool for designers. By using simple languages such as JavaScript in p5.js, artists and makers can create everything from interactive typography and textiles to 3D-printed furniture to complex and elegant infographics--Provided by publisher
Přeloženo z němčiny
Keywords: design; vizuální umění; programovací jazyky; počítačem podporované navrhování; JavaScript (programovací jazyk); visual art; programming languages; computer-aided learning; JavaScript (programming language); kolektivní monografie; collective monographs